RFID Technology in Healthcare Industry: Its Challenges and Requirements - Peivand Bastani; Roxana Sharifian; Saeid Ebrahimi; Yousef Mehdipour; Mojdeh Derahaki (مجله انفورماتیک سلامت و زیست پزشکی, 2016)
Introduction: Nowadays, the health care providers are faced with limited resources and rising costs. Information technology (IT) provides tools and processes required for measurement and control of the process and ultimately improves patient care in the centers of healthcare provider. In this regard, RFID is one of the new technologies and applications that benefits the healthcare industry. But its application in healthcare industry is faced with a lot of challenges and requirements that are discussed in this study.